A Simple Model of Health Insurance Competition - Alexander Kemnitz (Verein für Socialpolitik, 2010)
This paper investigates competition between health care insurance companies under different funding regulations. We consider two alternatives advanced in recent German health care reform discussions: competition by contribution rates (health contributions) and by fees (health premia). We find that competition by contributions can yield lower company profits and higher consumer welfare than competition by premia when switching between insurance companies is costly.
Keywords: I11; I18; D43; 330; Health Care Reform; Competition; Consumer Choice